Peran Kegiatan Muhadhoroh dalam Meningkatkan Kepercayaan Diri Peserta Didik SD Muhammadiyah Inovatif Mlarak - Mariana, Atika Nur; Laksana, Sigit Dwi; Sumaryanti, Lilis; Qomariyah, Sri Nurul (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2025)
Self-confidence is an attitude and belief in all one's abilities. The existence of problems in everyday life in terms of lack of self-confidence in students is something that must be considered. Self-confidence can be formed and increased through activities that can train students' courage, one of which is through activities muhadhoroh. SD Muhammadiyah Inovatif Mlarak facilitates students to increase their self-confidence through activities muhadhoroh which is held every Saturday. The method in this research uses a qualitative approach with a case study method, where data collection techniques use observation, interviews, and filling out questionnaires. Research findings show that through activities muhadhoroh at the SD Muhammadiyah Inovatif Mlarak, it was able to increase students' courage, and many students felt happy to come forward and appear in front of their friends. Students are said to have good self-confidence when they dare to go forward in front of other people without feeling nervous and are able to look at other people who are audience. The implications of this research show that the more students practice speaking or appearing in front of many people, the more they will become accustomed to their courage and self-confidence, which of course will support them to shape and develop their potential in order to achieve achievement. So, it can be concluded that the implementation of activities muhadhoroh at the SD Muhammadiyah Inovatif Mlarak can increase self-confidence well, which in turn can help students to increase their potential.